Adapting the short form of the Coping Inventory for Stressful Situations into Chinese - Li C (Dove Medical Press, 2017)
Chun Li,1 Qing Liu,2 Ti Hu,3 Xiaoyan Jin1 1International School of Chinese Studies, Northeast Normal University, Changchun, 2Department of Nuclear Medicine and Medical PET Center, The Second Hospital of Zhejiang University School of Medicine, Zhejiang University, Hangzhou, 3School of Physical Education and Sports, Beijing Normal University, Beijing, People’s Republic of China Objectives: The Coping Inventory for Stressful Situations (CISS) is a measurement tool for evaluating stress that has good psychometric properties. We investigated the applicability of a short-form version of the CISS in a large sample of Chinese university students. Methods: Nine hundred and seventy-two Chinese university students aged 18–30 years (mean =20.15, standard deviation =3.26) were chosen as subjects, of whom 101 were randomly selected to be retested after a 2-week interval. Results: The results of a confirmatory factor analysis revealed that the root mean square error of approximation of a four-factor model was 0.06, while the comparative fit index was 0.91, the incremental fit index was 0.93, the non-normed fit index was 0.91, and the root mean residual was 0.07. The Cronbach’s α coefficients for the task-oriented, emotion-oriented, distraction, and social diversion coping subscales were 0.81, 0.74, 0.7, and 0.66, respectively. The 2-week test–retest reliability was 0.78, 0.74, 0.7, and 0.65 for the task-oriented, emotion-oriented, distraction, and social diversion coping subscales, respectively. In the Chinese version of the CISS short form, task-oriented coping was positively correlated with positive affect and extraversion and negatively correlated with neuroticism; emotion-oriented coping was negatively correlated with extraversion and positively correlated with negative affect, anxiety, and neuroticism; distraction coping was positively correlated with neuroticism, extroversion, anxiety, positive affect, and negative affect and negatively correlated with psychoticism; and social diversion coping was positively correlated with extroversion and positive affect and negatively correlated with psychoticism. Conclusion: The Chinese version of the CISS short form is satisfactorily valid and reliable among Chinese university students. Keywords: stress, coping, factor analysis, reliability, validity, Chinese university students